1982
DOI: 10.1070/qe1982v012n06abeh005221
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the duration of fluctuating picosecond optical pulses

Abstract: A compact arrayed-waveguide grating (AWG) using multiple-arrowhead structures has been proposed. Arrowhead structures are useful for achieving low-cost and highly integrated waveguide devices because of their compactness. Therefore, the use of multiple-arrowhead structures enables us to achieve high-resolution AWGs with a channel spacing of less than 10 GHz, and we have already fabricated an 8-channel, 25-GHz-spacing AWG using a single-arrowhead structure, a 16-channel, 100-GHzspacing AWG using a double-arrowh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Birmontas et al . extended Van Stryland's analysis to include variations in pulse energy as well as duration and showed that the autocorrelation underestimates the average pulse length of unstable trains when the fluctuations in pulse power and length are correlated. It took more than a decade to unveil the physics behind the observed unstable synchronously pumped mode‐locking and to find a means for stabilization of the mode‐locking process .…”
Section: Historical Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Birmontas et al . extended Van Stryland's analysis to include variations in pulse energy as well as duration and showed that the autocorrelation underestimates the average pulse length of unstable trains when the fluctuations in pulse power and length are correlated. It took more than a decade to unveil the physics behind the observed unstable synchronously pumped mode‐locking and to find a means for stabilization of the mode‐locking process .…”
Section: Historical Overviewmentioning
confidence: 99%
“…The closest pulse profile was a single-sided exponential pulse; however, Van Stryland [35] argued that the autocorrelations were also consistent with a train of Gaussian pulses with a distribution of pulse widths. Birmontas et al [36] extended Van Stryland's analysis to include variations in pulse energy as well as duration and showed that the autocorrelation underestimates the average pulse length of unstable trains when the fluctuations in pulse power and length are correlated. It took more than a decade to unveil the physics behind the observed unstable synchronously pumped mode-locking and to find a means for stabilization of the mode-locking process [37,38].…”
Section: Historical Overviewmentioning
confidence: 99%
“…Subsequent experiments have yielded pulse durations of the same order (Lornpre et a1 1975, Al-Obaidi et a1 1975) (see Liu and Yen (1979) for results in an unstable resonator). Bechtel and Smith (1975) and Birmontas et al (1978) studied statistical fluctuations in the pulse widths and energies, while Zherikhin et a1 (1974a) and Chekalin et a1 (1974) investigated the effect of an intracavity telescope on the process of formation of ultrashort pulses in their Nd :YAG system (see § 6.3.3 for a detailed interpretation of this work). While Siebert and Montry (1978) showed that self-phase modulation (SPM) in YAG led to temporal fragmentation of the pulses in the far field, Sauteret and Novaro (1980), who used a novel Young's slit technique for diagnosing phase structure, stressed that the linear frequency sweeps they recorded were not in themselves consistent with self-phase modulation effects.…”
Section: The Recovery Time ( T L B )mentioning
confidence: 99%